International Trade Policies : The Uruguay Round and Beyond, Volume I. Principal Issues - Subramanian, Arvind (World Economic Outlook; World Economic Outlook ;, 1995)
This paper analyzes the achievements of the Uruguay Round, and issues with the post-Uruguay Round agenda. The paper highlights that the conclusion of the Uruguay Round is a major achievement in international trade relations and a crucial element in promoting world trade and growth in the medium term. It arrested the deterioration in the trading environment and created a strengthened framework for future trade relations, thereby boosting business and investment confidence. It also provides positive outcomes in several areas, including market liberalization and strengthening of rules and institutional structures.